2011
DOI: 10.1097/aog.0b013e3181f9b749
|View full text |Cite
|
Sign up to set email alerts
|

Transmural Vaginal-to-Bladder Injury From an Obstructed Labor Pattern

Abstract: These findings may provide evidence of the transmural vaginal-to-bladder damage that can occur from obstructed labor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…If a woman in an affluent country develops a serious injury from obstructed labor, the event is remarkable enough to be written up and published as a case report in a medical journal [46,47]. In contrast, there are millions of unrepaired obstetric fistulas in sub-Saharan Africa and south Asia.…”
Section: Discussionmentioning
confidence: 99%
“…If a woman in an affluent country develops a serious injury from obstructed labor, the event is remarkable enough to be written up and published as a case report in a medical journal [46,47]. In contrast, there are millions of unrepaired obstetric fistulas in sub-Saharan Africa and south Asia.…”
Section: Discussionmentioning
confidence: 99%
“…None of these were diagnosed prior to laparotomy. Allen et al 4 reported a case of a patient presenting with obstructed labor. Examination revealed a crowning fetal head, no fetal heart tones, and purulent vaginal discharge.…”
Section: Discussionmentioning
confidence: 99%
“…However, this is exceedingly rare in developed world [2]. Even rarer is the occurrence of vaginal rupture.…”
Section: Discussionmentioning
confidence: 99%